Answer:
A or 53 squared
Step-by-step explanation:
Answer:
Just try to make it make sense to you.
Step-by-step explanation:
For instance, a + 1 = 5
a = 4
We know that we should switch the terms as when it comes to normal numbers ,10 + 1 = 11 , 10 = 11-1. Therefore, the only trick is not to memorise, but try to understand the logic behind it. Hope this helps in some way???
The part that represents the solution to the inequality will be Part B shaded below first line and above second line.
<h3>How to depict the inequality?</h3>
From the information given, the equation of the first line will be:
y - 3 = (-3 - 3/2 + 4)(x + 4)
y - 3 = -1(x + 4)
y + x = -4 + 3
x + y = -1
The equation of the second line will be:
y + 3 = -1(x + 4)
y = x + 4 - 3
y = x + 1
This is plotted on the graph attached.
From the systems of equations, the statement that is correct about the two systems of equations is that They will have the same solution because the first equation of System B is obtained by adding the first equation of System A to 3 times the second equation of System A.
Learn more about inequalities on:
brainly.com/question/12215820
#SPJ1
Multiply:
6•12=72
Then, you subtract 39 from 72:
72-39=33
33 containers would still need to be set up.
Answer:
It was Romania, so Spain.